Manusia Ideal Dalam Prespektif Tasawwuf dan Filsafat (Studi Komperatis Pemikiran Ibnu Araby dan Nietsche Tentang Manusia) - Fithriyah, Ainul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The variety of thoughts about the optimal attainment of human self and the satisfaction of human life is what may have made Arthur Schopenhauer (1788-1868) deny all worldly phenomena. He saw that the world was full of suffering. Humans, as the supreme product of the basic activities of the world, are in fact the most unfortunate creatures. Therefore, humans will be able to achieve happiness when they are able to kill passions and cravings. Studies on the optimal achievement of humans and the meaning of human life from the two figures above, are still important and beneficial to do. Because the concept of the ideal human being is a model and example for us that we can emulate or maybe we can make it happen if we feel fit and believe in the truth. But the question might arise, is it still relevant to study the thoughts of long-dead figures such as Ibn Arabi and Neitzsche? in the opinion of the author, the study of their thinking is still relevant. Because in their thoughts are contained eternal pearls, and because of the peculiarity of each thought. This is evident if we pay attention today, where the thoughts of the two figures are still the subject of study in various countries, both in the West and the East. The works that examine Nietzsche's thoughts about the Ubermensch man include the work of Chairul Arifin, entitled The will to power: Briedrich Nietzsche. This book discusses Nietzsche's views on human beings and his anti-theism. These two thoughts are then connected by the author of this book with Nietzsche's main thought, namely the will to power. And in one of its chapters, the book also examines the concept of Ubermensch Nietzsche. Another work that addresses Nietzsche and Nietzsche's main ideas, including Ubermensch in a separate chapter is Nietzsche by St Sunardi. Besides that, there are other books. Of the books mentioned above and others to the best of the author's knowledge, there has never been found a work that specifically compares Ibn Arabi's insan kamil concept and Nietzsche's Ubermensch concept.